Pneumococcal meningitis by an unusual serotype: a case report - Soares, Catarina B.; Boavista, Sofia; Rodrigues, Hugo; Branco, Mariana (International Journal of Contemporary Pediatrics, 2025)
With the evolution of the vaccination and antimicrobian pressure, there has been changes in the Streptococcus pneumoniae serotypes becoming more frequent the ones not included in the vaccines. Herein this report presents a clinical case of a 11-month-old boy with meningitis due to Streptococcus pneumoniae serotype 24F. This serotype is not included in the vaccines available in Portugal. Therefore, we present this clinical case to explore and understand the changes of bacterial epidemiology.